Characteristics of women with uterine prolapse at Dr. Soetomo Hospital, Surabaya, Indonesia - Akhmad Risdianto; Hari Paraton; Gatut Hardianto; Eighty Mardiyan; Azami Denas; Tri Hastono (Universitas Airlangga, 2020)
Objective: The aim of this study was to analyze the incidence, sociodemographic characteristic and risk factor patient with uterine prolaps in Dr. Soetomo Hospital period 2016.Materials and Methods: This study using observational descriptive study.Results: There were 41 subjects of this study with uterine prolaps. which is mostly on age 51-60 years old (37%). Uterine prolaps grade III was the frequent (29%). Uterine prolaps mostly happened in multiparity (93%) than primiparity (7%). All of the prolaps uterine patient giving birth by vaginal delivery. Uterine prolaps most commonly occures after menopause (80%). 28 patient (68%) with uterine prolaps underwent surgery.Conclusion: The incidence of uterine prolaps dramatically increase especially uterine prolaps grade III. Multiparity, vaginal delivery, and post menopausal were the main risk factor. This could be reduce the quality of life.